Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja terhadap Produktivitas Kerja pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gunungkidul - Huda Pramana; Jajuk Herawati; Epsilandri Septyarini (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to analyze (1) the effect of work motivation on work productivity (2) The effect of work discipline on work productivity. (3) the influence of the work environment on work productivity. (4) the effect of work motivation, work discipline and work environment on work productivity. The population in the study were all employees of the Gunungkidul Regency Population and Civil Registration Office, totaling 66 people. All employees are taken data or census using a questionnaire instrument. The data analysis methods used in this study are validity test, reliability test, classic assumption test, and multiple linear regression test with the IBM SPSS Version 26 tool program. The data analysis was carried out to identify independent variables that affect the dependent variable. The results of the study found that (1) work motivation has a positive and insignificant effect on work productivity. (2) Work discipline has a positive and significant effect on work productivity. (3) The work environment has a positive and significant effect on work productivity. (4) work motivation, work discipline and work environment together have a significant positive effect on work productivity. Keywords: Work Motivation, Work Discipline, Work Environment, Work Productivity